# (t-5)(5t-3)

sciencesolve | Teacher | (Level 3) Educator Emeritus

Posted on

The request of the problem is vague, hence, supposing that you need to multiply the brackets yields:

`(t-5)(5t-3) = t*5t + t*(-3) - 5*(5t) - 5*(-3)`

`(t-5)(5t-3) = 5t^2 - 3t - 25t + 15`

`(t-5)(5t-3) = 5t^2 - 28t + 15`

Hence, evaluating the product of brackets yields `(t-5)(5t-3) = 5t^2 - 28t + 15` .

If the problem requests to solve for t the equation `(t-5)(5t-3) = 0` ,then you need to perform the following steps such that:

`(t-5)(5t-3) = 0 => {(t-5=0),(5t-3 = 0):} => t = 5 , t = 3/5`

Hence, evaluating the solutions to the equation yields `t = 5 , t = 3/5.`

aa42 | Student, Grade 10 | (Level 1) Honors

Posted on

Multiplying (5t-3)and (t-5)\

5t - 3

X      t - 5

-25t - 15

5t^2-3T  X

5t^2-28t+15

We get 5t^2-28t+15 which is the required answer.

tub51463 | Middle School Teacher | (Level 1) eNoter

Posted on

(t-5)(5t-3)

You have to use the FOIL method

F: first

t*5t = 5t^2

O: outr

t*-3 = -3t

I: inner

-5*5t = -25t

L: last

-5*-3 = 15

now put it all together:

5t^2 - 3t - 25t + 15

5t^2 - 28t + 15